The Interactions Between Candida albicans and Mucosal Immunity - Zhou, Yujie; Cheng, Lei; Lei, Yu L.; Ren, Biao; Zhou, Xuedong (Frontiers in Microbiology, 2021)
Mucosa protects the body against external pathogen invasion. However, pathogen colonies on the mucosa can invade the mucosa when the immunosurveillance is compromised, causing mucosal infection and subsequent diseases. Therefore, it is necessary to timely and effectively monitor and control pathogenic microorganisms through mucosal immunity. Candida albicans is the most prevalent fungi on the mucosa. The C. albicans colonies proliferate and increase their virulence, causing severe infectious diseases and even death, especially in immunocompromised patients. The normal host mucosal immune defense inhibits pathogenic C. albicans through stepwise processes, such as pathogen recognition, cytokine production, and immune cell phagocytosis. Herein, the current advances in the interactions between C. albicans and host mucosal immune defenses have been summarized to improve understanding on the immune mechanisms against fungal infections.